Anticancer activity of oleanolic acid and its derivatives: Recent advances in evidence, target profiling and mechanisms of action - Zhong-Yuan Tang (Elsevier, 2022)
Oleanolic acid (OA, 3 β - hydroxyoleanolic acid-12-en-28-oic acid) is a pentacyclic triterpenoid present in many plants. As a new framework for development of semi synthetic triterpenoids, OA is of great significance in the discovery of anticancer drugs. Some of these derivatives, such as CDDO (2-cyano-3,12-dioxooleana-1, 9 (11)-dien-28-oic acid) have been verified in clinical trials, while other derivatives studied previously, such as SZC014, SZC015 and SZC017 (OA derivatives respectively), are also candidate drugs for cancer treatment. This paper reviews the preclinical studies, literature evidence, target analysis and anticancer mechanism of OA and its derivatives. The mechanism of action of its derivatives mainly includes anti-cancer cell proliferation, inducing tumor cell apoptosis, inducing autophagy, regulating cell cycle regulatory proteins, inhibiting vascular endothelial growth, anti angiogenesis, inhibiting tumor cell migration and invasion. In recent years, the molecular mechanism of OA and its derivatives has been elucidated. These effects seem to be mediated by the alterations in a variety of signaling pathways induced by OA and its derivatives. In conclusion, OA and its derivatives are considered as important candidate drugs for the treatment of cancer, indicating that OA and its derivatives have the potential to be used as anticancer drugs in practice.